Model Predictive Control of Autonomous Underwater Vehicles Based on Horizon Optimization - sudirman sudirman; Mochammad Rameli; Rusdhianto Effendi (Department of Electrical Engineering ITS and FORTEI, 2020)
Heading control of Autonomous Underwater Vehicle (AUV) using Model Predictive Control (MPC) gives a good performance. Varying the length of the horizon provides a variety of performance. This paper is made in order to find out how many optimal horizons are needed to obtain the highest efficiency of energy use in AUV. Test results show a positive correlation between the length of the horizon and the amount of energy used. The optimal horizon obtained is then tested on several different trajectories.Keywords: autonomous underwater vehicle, horizon optimizatoin, model predictive control.